POVERTY ALLEVIATION STRATEGY FOR OIL PALM PLANTATION WORKERS IN OGAN KOMERING ULU REGENCY - Djati, Sri Dewa Barata Kusuma; Munajat, Munajat; Efrianti, Rini (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
The aim of this research is to analyze the appropriate strategy for poverty alleviation among oil palm workers in Ogan Komering Ulu (OKU) Regency. This research was analyzed using the SWOT method. The results showed that based on the Strengths, Weaknesses, Opportunities, and Threats that exist among oil palm workers in Ogan Komering Ulu Regency, it can be concluded that the right strategy for poverty alleviation among oil palm workers in Ogan Komering Ulu Regency. The strategy is a poverty alleviation strategy that can be carried out by palm oil workers and the Ogan Komering Ulu Regency Government is to improve the quality of self (HR), manage natural resources (SDA) properly, maintain facilities and infrastructure properly, guarantee the welfare of palm oil workers and provide legal assistance for palm oil workers who experience injustice.